Training in the market economy : challenges and answers - Simonics, István [Herausgeber] (National Institute of Vocational Education, Budapest, 1997)
"The National Institute of Vocational Education held its first vocational training research seminar on December 6, 1995 under the titel 'Training in Market Economy: Challenges and Answers'. This publication contains the edited versions of lectures made at the research seminar and the presentation of the international relations of the Hungarian Ministry of Labour and the National Institute of Vocational Education." This book contains contributions by Laszlo Alex (BIBB) und Tibor Adler (BIBB): 'The main fields of vocational training research in Germany' and 'Vocational training research to lay the foundations of the programs'. (Excerpt, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Bildungspersonal; Arbeitsmarkt; Estland; Tschechische Republik; Rumänien; Ungarn; Bundesrepublik Deutschland